Components and Indicators of Digital Teacher Competency in Schools under the Provincial Administration Organization - Pakdee Siripan,; Surachet Noirid, (Journal of Educational Issues, 2024)
In teaching management in modern times, teachers must have digital competence because nowadays digital platforms are being used in teaching and learning in a variety of ways. The objectives of this research aim to study the components and indicators of digital teacher competency in schools under the provincial administrative organization. The tools used to collect the data were the assessment form for the suitability of components and indicators, which was confirmed by seven experts. The results of the study showed that the components of digital teacher competency in schools under the provincial administrative organization are four components: (1) digital literacy; (2) use of digital tools and media; (3) problem-solving using digital tools; and (4) digital adaptation and transformation. Overall, each element is the most appropriate. The components and indicators of digital literacy are best suited. The digital tool and media use components and indicators are the most appropriate. The components and metrics for problem-solving with digital tools are optimal. The elements and indicators of digital adaptation and transformation are most appropriate.